NEGARA PANCASILA SEBAGAI DARUL ‘AHDI WA AL-SYAHADAH Wawasan dan Kontribusi Muhammadiyah Bagi NKRI - Syamsul Hidayat (Universitas Muhammadiyah Surakarta, 2016)
Muhammadiyah figures contributed greatly to the continuity of the Republic of Indonesia, including in the preparation of the foundations of the State. At the time of the first principle was proposed by Ki Bagus, it asserted that belief in one God means monotheism (tauhidullah) for Muslims. With this principle, Muhammadiyah will keep the deal as long as the deal is still providing benefit for Islam and Muslims, especially in Indonesia. That is Darul Ahdi, this deal is significant and mean Darussalam (peace Nation), Peace Nation between Muslims and non-Muslims, as well as countries that provides peace, freedom and the guarantee for the enforcement of oneness belief and practice the teachings of Islam for its followers. While Pancasila State as Dar al-Shahadah is witness state and proofing that Muslims should play an active role to give meaning to the understanding, appreciation and practicing Pancasila with the Islamic values, which is there is no contradiction between the two.